1998
DOI: 10.1209/epl/i1998-00456-2
|View full text |Cite
|
Sign up to set email alerts
|

Broadband detection of squeezed vacuum: A spectrum of quantum states

Abstract: We demonstrate the simultaneous quantum state reconstruction of the spectral modes of the light field emitted by a continuous wave degenerate optical parametric amplifier. The scheme is based on broadband measurement of the quantum fluctuations of the electric field quadratures and subsequent Fourier decomposition into spectral intervals. Applying the standard reconstruction algorithms to each bandwidth-limited quantum trajectory, a "spectrum" of density matrices and Wigner functions is obtained. The recorded … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…Squeezed vacuum can be generated with a variable but frequency-independent squeezing angle λ (see for example [39]). A frequency-dependent squeezing angle can be obtained subsequently by filtering the initial squeezed light through detuned FabryPérot (FP) cavities, as proposed by Kimble et al [14], which can rotate the quadratures in a frequency dependent way.…”
Section: Figmentioning
confidence: 99%
“…Squeezed vacuum can be generated with a variable but frequency-independent squeezing angle λ (see for example [39]). A frequency-dependent squeezing angle can be obtained subsequently by filtering the initial squeezed light through detuned FabryPérot (FP) cavities, as proposed by Kimble et al [14], which can rotate the quadratures in a frequency dependent way.…”
Section: Figmentioning
confidence: 99%
“…x 0 e −t 2 dt we find R(τ ) = 10 · log[erf(2 √ 2τ )], 9 In the calculation one first splits the expressions into two equal parts and than performs ω → −ω in one of the parts, which after subsequent exchange p ↔ k allows to stretch the ω integration to the whole R. 10 Typically the field is measured on BHD with local oscillator LO [1] (mainly because no device is sensitive enough to measure the vacuum fluctuations directly). The frequency of the LO plus the frequency at which the output of BHD is analyzed give the center ω0 of the sensitivity function µp.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…|f g = d 3 p d 3 k f (p)g(k)a † (p)a † (k)|Ω , where for simplicity the polarization was disregarded. 1 of fields, eg. electromagnetic [9], Dirac [3], even in the situation where the fields propagate in a curved spacetime (which is far more difficult than anything we shall present here).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental demonstration * stefan.ataman@eli-np.ro † anca.preda10@gmail.com ‡ r.ionicioiu@theory.nipne.ro with a MZI [14] soon followed, proving the usability of the concept in practical measurements. Over the next decades both theoretical and experimental studies have showed how to improve the sensitivity of a MZI fed by both a coherent and a squeezed vacuum input [15][16][17][18]. In a quantum context, however, the phase sensitivity is bounded by the Heisenberg limit [4,11,[19][20][21], ∆ϕ HL ∼ 1/ N , and this limit is fundamental [22].…”
Section: Introductionmentioning
confidence: 99%